Supervisor as a classroom instructor [filem jalur] - Resources for Education and Environment, inc (Produced by Resources for Education and Environment Addison-Wesley Pub., 1970)
Contents : 1. The teaching - learning process. 2. Communications and learning. 3. Preplanning and objectives. 4. Helping the learner learn. 5. Effective teaching techniques. 6. Evaluation and follow-up.